2015
DOI: 10.1097/mop.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

Hirschsprung's associated enterocolitis

Abstract: Purpose of Review Hirschsprung’s Disease (HSCR) is characterized by an absence of ganglion cells in the distal hindgut, extending from the rectum to a variable distance proximally, and results from a failure of cranial-caudal neural crest cell migration. Hirschsprung’s-Associated Enterocolitis (HAEC) is a condition with classic manifestations that include abdominal distention, fever and foul-smelling stools, and is a significant and life-threatening complication of HSCR. The purpose of this review is to critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 31 publications
0
50
0
1
Order By: Relevance
“…To test this expulsion-based mechanism more directly, we assessed whether the abundance of Δmot and Δche could be rescued in ret −/− mutant zebrafish hosts, which have reduced intestinal transport because of a dysfunctional enteric nervous system [32,42]. Humans with ret mutations can develop Hirschsprung disease, which is an affliction characterized by intestinal dysmotility and altered gut microbiome composition [43,44]. Strikingly, we found that the intestinal abundances of both Δmot and Δche were fully rescued to wild-type levels in ret −/− mutant animals ( Fig 3B).…”
Section: Plos Biologymentioning
confidence: 99%
“…To test this expulsion-based mechanism more directly, we assessed whether the abundance of Δmot and Δche could be rescued in ret −/− mutant zebrafish hosts, which have reduced intestinal transport because of a dysfunctional enteric nervous system [32,42]. Humans with ret mutations can develop Hirschsprung disease, which is an affliction characterized by intestinal dysmotility and altered gut microbiome composition [43,44]. Strikingly, we found that the intestinal abundances of both Δmot and Δche were fully rescued to wild-type levels in ret −/− mutant animals ( Fig 3B).…”
Section: Plos Biologymentioning
confidence: 99%
“…It may be possible that the spleen torsion of our patient is related to altered endothelin receptor type B function due to EDNRB mutations. Also, in patients with Hirschsprung's disease, altered goblet cell structures and functions in aganglionic segments of bowel may be responsible for the recurrent enterocolitis [16]. The complex interactions between EDNRB mutations, immune dysfunction, and changes in gut functional conditions due to Hirschsprung's disease could be associated with recurrent enteritis shown in our patient.…”
Section: Discussionmentioning
confidence: 77%
“…These can be caused by variations in the components and amount of mucus, immunological deficiency, either local or systemic, with deficient white cell function, mucosal immunity defects, increased prostaglandin E1 activity, impaired motility associated with protein sensitization, and sucrase-isomaltase deficiency. 11,12,[16][17][18][19][20] These conditions could be the expression of the complex genetics of HD. 21 Increased HE risk in patients with Down syndrome, 22,23 cartilage-hair hypoplasia, 24 family history of HD, and female sex point to a possible genetic contribution to the etiology of HE.…”
Section: Discussionmentioning
confidence: 99%